2008
DOI: 10.1002/rcm.3670
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography/time‐of‐flight mass spectrometry based metabonomic approach to differentiating hypertension‐ and age‐related metabolic variation in spontaneously hypertensive rats

Abstract: Metabonomics is a systematic approach to the study of in vivo metabolic profiles and therefore allows deep insight into and a better understanding of the pathogenesis of disease. To characterize the development of hypertension, a hypertensive animal model, the spontaneously hypertensive rat (SHR), and its normotensive control, the Wistar Kyoto (WKY) rat, were investigated and their blood plasma analyzed using the high-throughput metabolomic tool, gas chromatography/time-of-flight mass spectrometry (GC/TOFMS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 20 publications
2
47
0
2
Order By: Relevance
“…The genome-wide mapping of human loci has linked many candidate genes to essential hypertension [6,7] , although none of them has been widely confirmed in different population groups. Recently, the metabolic profiling of hypertension has drawn the attention of researchers [8][9][10][11][12][13][14] . Brindle and colleagues found a relationship between serum metabolic profiles and blood pressure in clinic patients [9] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genome-wide mapping of human loci has linked many candidate genes to essential hypertension [6,7] , although none of them has been widely confirmed in different population groups. Recently, the metabolic profiling of hypertension has drawn the attention of researchers [8][9][10][11][12][13][14] . Brindle and colleagues found a relationship between serum metabolic profiles and blood pressure in clinic patients [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Brindle and colleagues found a relationship between serum metabolic profiles and blood pressure in clinic patients [9] . Our previous studies of clinical patients and spontaneously hypertensive rats (SHRs) clearly showed that metabolomic patterns associated with hypertension were different from those of the normotensive controls, demonstrating the obviously perturbed metabolism of hypertension [12][13][14] . Hypertension is inherently involved in metabolic syndrome, including hyperlipidemia and diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, genomic techniques recently were used to identify a genetic variation within the FOXO3A gene that is strongly associated with human longevity (Willcox et al 2008). Metabolomic techniques identified a close association between free-fatty acids and hypertension in the salt-dependent hypertensive rodent, suggesting that this powerful approach may be useful in identifying potential biomarkers of hypertension and the physiological consequences of aging (Lu et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…This methodology has also been applied in aging studies in several species including Caenorhabditis elegans, fruit fly, rodents, dogs, and humans (Kristal and Shurubor 2005;Mishur and Rea 2012). In mammalian studies, carnitines, fatty acids, and other metabolites associated with energy metabolism, lipid metabolism, nucleic acid metabolism, and oxidative stress were shown to be perturbed with age (Williams et al 2005;Granger et al 2007;Lu et al 2008;Lawton et al 2008).…”
mentioning
confidence: 99%